A case of cerebral haemorrhage—can Ginkgo biloba be implicated?. Issue 904 (1st February 2001) - Benjamin, J; Muir, T; Briggs, K; Pentland, B
Abstract : The case of a 56 year old man who suffered a spontaneous intracerebral haemorrhage after regular self medication with the herbal preparation, Ginkgo biloba leaf extract is described, and the possible association is discussed.